TAFSIR ILMU TENTANG MENGELOLA WAKTU - M. Rais Umam Bisri (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2020)
ABSTRACT In the teachings of Islam, Allah instructs His servants to make the best use of time, because time is very important, so taking advantage of time is Allah's mandate to His creatures. Because of the urgency of the role of time, Allah repeatedly swore by using words denoting certain times. Al-Qur'an also uses terms which indicate different times. In the Koran, the disclosure of time has two forms, namely terms which indicate a clear duration of boundaries such as ghada> h, 'ashr, bukrah, ashi> la,' asyiyya ',' isya ', layl, naha> r, yawm, syahr, 'am, sanah. while the terms which indicate the duration with no clear boundaries such as waqt, dahr, ajal, hin and sa'ah. The term which shows the duration with a clear boundary contains certain times or momentum of virtue, time to worship and also shows the time travel or rotation of the sun and moon where all these events can be known by humans. Meanwhile, the term which shows the duration with no clear boundaries contains the inevitability, resurrection, control of spirit and death, the determination of death, and resurrection and the Day of Judgment where it cannot be known by anyone, such as dahr is used for prolonged moments that the universe passes through in the life of the world. this is from the time He was created to the extinction of nature, death indicates the end time for something such as the end of human life, sa'ah indicates the end of the worldly life and the extinction of nature and so on.